A late recurrence of renal cell carcinoma as pancreatic metastases: a rare disease. (31st May 2013) - Kapoor, Rakesh; Kumar, Ritesh; Dey, P; Mittal, B R
Abstract : A man presented with multifocal pancreatic metastases 9 years after nephrectomy for renal cell carcinoma. He was managed with oral sunitinib. He had favourable response to treatment with excellent compliance.